Potential Future Applications of Postbiotics in the Context of Ensuring Food Safety and Human Health Improvement - Zorica Tomičić; Ljubiša Šarić; Ružica Tomičić (Antibiotics)
Postbiotics are defined as non-viable metabolites or compounds produced by probiotic microorganisms with significant impact on human health. The growing interest in postbiotics is supported by numerous studies due to their additional benefits over probiotics that show positive outcomes for specific conditions, as well as their application as biopreservatives in the food industry. Their potential in functional foods and therapeutic applications is increasingly recognized as they exhibit stability, safety, and diverse biological activities. As for their most important biological roles, postbiotics have been shown to have effective anti-inflammatory, antimicrobial, antioxidant, and anticancer properties, in addition to reducing food allergies. The application of postbiotics in functional foods contributes to improving intestinal health and reducing the risk of foodborne diseases. The concept of postbiotics is relatively new in the food industry. They offer a promising alternative to conventional food preservatives due to their ability to inhibit pathogenic bacteria and extend shelf life. Considering the diversity of postbiotic compounds and their significant biological activities, this review presents and discusses the mechanisms of action and future trends in their application in the food industry and their impact on human health. Increasing research and development in the production and formulation of postbiotics will play a key role in the upward trajectory of the market.